Banalities in Kelong Makassar - Asis Nojeng; Sakaria Sakaria; Nur Hasbi (Aksara, 2026)
This study aims to analyze the phenomenon of banality in Makassar kelong, namely the tendency of degradation of meaning due to commercialization, use outside its original cultural context, and the influence of digital media in its distribution. The research method used is a qualitative approach. This research was conducted from May to December 2025. The data sources for this study consist of primary and secondary data. Data collection techniques used are literature study, documentation, observation, data transcription, and data classification. Meanwhile, data analysis is carried out using data reduction techniques, data presentation, and drawing conclusions, then the final stage is data validity. The results of the study show that banality in Makassar kelong occurs in several forms, such as simplification of meaning, adaptation that eliminates philosophical values, and dissemination through social media that tends to prioritize entertainment aspects over cultural substance. This phenomenon shows that kelong is no longer only part of a sacred oral tradition, but has also undergone a transformation into a pragmatic popular cultural product. This study provides a theoretical contribution to the field of oral literature by combining semiotics and banality. These findings serve as a reflection to preserve kelong so that it does not lose its depth of meaning in more modern cultural flows. AbstrakPenelitian ini bertujuan untuk menganalisis fenomena banalitas dalam kelong Makassar, yaitu kecenderungan degradasi makna akibat komersialisasi, penggunaan di luar konteks budaya aslinya, serta pengaruh media digital dalam persebarannya. Metode penelitian yang digunakan adalah pendekatan kualitatif. Penelitian ini dilakukan dalam rentang waktu Mei hingga Desember 2025. Sumber data penelitian ini terdari dari data primer dan sekunder. Teknik pengumpulan data yang digunakan adalah studi pustaka, dokumentasi, observasi, transkripsi data, dan klasifikasi data,. Sementara itu, analisis data dilakukan dengan menggunakan teknik reduksi data, penyajian data, dan penariksan kesimpulan, kemudian tahap akhir adalah keabsahan data. Hasil penelitian menunjukkan bahwa banalitas dalam kelong Makassar terjadi dalam beberapa bentuk, seperti simplifikasi makna, adaptasi yang menghilangkan nilai filosofis, serta penyebaran melalui media sosial yang cenderung mengutamakan aspek hiburan dibandingkan substansi budaya Fenomena ini menunjukkan bahwa kelong tidak lagi hanya menjadi bagian dari tradisi lisan yang sakral, tetapi juga mengalami transformasi menjadi produk budaya populer yang bersifat pragmatis. Penelitian ini memberikan kontribusi teoretis dalam bidang sastra lisan dengan memadukan semiotika dan banalitas. Hasil temuan ini berfungsi sebagai refleksi untuk melestarikan kelong agar tidak kehilangan kedalaman maknanya dalam arus budaya yang lebih modern.